2016
DOI: 10.1111/icad.12196
|View full text |Cite
|
Sign up to set email alerts
|

Species richness of cuckoo bumblebees is determined by the geographical range area of the host bumblebee

Abstract: The geographical range area of host hypothesis predicts that regionally widespread host species are able to support higher local parasite species richness. In this study, we investigated the macro‐ecological patterns in cuckoo bumblebee species richness in relation to the geographical range area of their bumblebee hosts (Hymenoptera: Apidae: Bombini). The cuckoo bumblebees live in naturally fragmented environments composed of host bumblebee colonies upon which they are exclusively dependent. We collected data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Obligate brood parasites such as cuckoo bumblebees, are entirely dependent on their hosts for reproduction, thus the host can be considered a resource (Steffan-Dewenter and Schiele, 2008;Suhonen et al, 2016). Therefore, elements of their community structure are likely to be driven by those of their host (Murray et al, 2009;Suhonen et al, 2015;Suhonen et al, 2016). Therefore, we also predicted that cuckoo bumblebee community metrics would be driven by the community metrics of their hosts.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Obligate brood parasites such as cuckoo bumblebees, are entirely dependent on their hosts for reproduction, thus the host can be considered a resource (Steffan-Dewenter and Schiele, 2008;Suhonen et al, 2016). Therefore, elements of their community structure are likely to be driven by those of their host (Murray et al, 2009;Suhonen et al, 2015;Suhonen et al, 2016). Therefore, we also predicted that cuckoo bumblebee community metrics would be driven by the community metrics of their hosts.…”
Section: Introductionmentioning
confidence: 81%
“…As such, further research is needed to fully understand their ecology (Lhomme and Hines, 2018) and evidence suggests that they are even more at risk of extinction than their hosts (Suhonen et al, 2015). Whilst the ecology and community metrics of hosts will affect cuckoo community metrics due to their reproductive dependency on their host (Suhonen et al, 2016), the results suggest that perhaps cuckoos can respond differently from their hosts to environmental factors, such as farming practice. Differential effects of farming practices have previously been found among groups within the bee superfamily, for example among honeybees, bumblebees and solitary bees (Le Féon et al, 2010;Holzschuh et al, 2008) and are even found within the Bombus genus (Rundlöf et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the resource distribution hypothesis [10,11], widespread species are able to support a higher parasite diversity than are species with more restricted geographical ranges. Large GRS and large population size of host species have often been shown to correlate with high parasite prevalence and diversity [12 -16], so that rare hosts tend to have fewer [8] or no [15] parasite species. However, it is poorly known how GRS and phylogenetic relationships among actual and potential host species affect the probability of host switching by parasites [9].…”
Section: Introductionmentioning
confidence: 99%